PREVIOUS KNOWLEDGE MEASUREMENT THROUGH THE USE OF A MATHEMATICAL SOFTWARE TO ESTABLISH IMPROVEMENT PLANS IN STUDENTS AT AN EDUCATIONAL INSTITUTION OF LA DORADA (CALDAS) - Hernández Molina, Oscar Julián
A measurement and evaluation of previous knowledge in the area of mathematics was carried out within the curricular framework of the Basic Learning Rights (DBA) for the 5th grade of primary school of the Ministry of National Education. Based on this analysis, a proposal was made to the educational institution under study, to adjust the contents that obtained low marks, recommending an improvement plan that responds to the need to train students and later mathematically competent citizens.   Proposal for the development and construction of mathematical software for grade 5 primary and be applied in the Educational Institution, offer a more attractive, interactive and intuitive work environment, allow to recreate different problems, situations or realities in the different contexts of the student and stop making it “less abstract”. Mathematical software is a program designed so that students and teachers can visualize a friendly interface to be able to respond to mathematical activities and processes in a more assertive way, with tools consistent with this digital age.